Bos Funds Allocation For Pilot Schools: Study On SDIT Bina Insan Qur'ani Cibatu-Garut - Ega Rahmat Pauzi; Imam Tabroni Tabroni (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2021)
Educational actors are still confused in setting funding priorities for the development of pilot schools. This paper is intended to understand the priority allocation of pilot school funding originating from BOS funds. This research uses a qualitative method with an action research approach. The theory used is the concept of allocation and budgeting from Nanang Fattah. The problem that arises is what kind of financing sector gets more budgeting in pilot schools. From the findings in the field, it was found that the largest portion of the allocation of BOS funds for three years was in the funding of salaries for teachers and education staff. The budget design of SDIT Bina Insan Qur'ani uses a model of budgeting by line item. However, every year there is a change in the budgeting format. This was done to simplify school spending.